تقييم فاعلية بعض الفطريات الناقصة كعوامل مكافحة حيوية تجاه الفطر الدعامي Bjerkandera adustus المسبب للعفن الأبيض في بعض مناطق الساحل السوري (Latakia University Journal -Biological Sciences Series, 2018)
In this research we studied the efficiency of the Deuteromycetes, Penicillium expansum, Trichoderma viride, T.harzianum and Fusarium oxysporum against Bjerkandera  adustus that causes white rot on the wood. The efficiency was evaluated in two ways, dual culture and volatile compounds. The results showed an inhibitory efficiency of the Deuteromycetes tested against B.adustus fungus, which differed depending on the fungus species tested and the method of test. The non-volatile compounds diffuse in the middle in the dual culture tests was more actively in the growth of B.adustus. The T.harzianum fungus had the highest efficiency in inhibiting the growth of wood rot fungus ,reaching inhibition rate of 70.59% after it T.viride came at a rate of 60.39%, then the two fungi P.expansum and F.oxysporum at a rate of 30.19% and 25.49%, respectively. The efficiency of Deuteromycetes differed depending on days of experience, and reached the highest percentage of inhibition in the ninth day of the experience, and the growth of Deuteromycetes stopped in different days depending on the type of anti-fungus. Volatile compounds for all Deuteromycetes showed stimulus effect for the growth of B.adustus. تم في هذا البحث تقييم فاعلية الفطريات الناقصة Fusarium oxysporum ،Penicillium expansum ، Trichoderma viride وT.harzianum ضد الفطر الدعاميBjerkandera adustus المسبب للعفن الأبيض على الأخشاب، تم ذلك بطريقتي الزراعات الثنائية والمركبات الطيارة. أوضحت النتائج فاعلية تثبيطية للفطريات الناقصة المضادة المختبرة تجاه الفطرB.adustus ، والتي اختلفت  باختلاف نوع الفطر المضاد وطريقة الاختبار. كانت المركبات غير الطيارة المنتشرة في الوسط في اختبارات الزراعات الثنائية، أكثر تأثيراً في نمو الفطر الدعامي، وقد امتلك الفطرT.harzianum الفاعلية الأعلى في تثبيط نمو الفطر المخرب للأخشاب، حيث بلغت نسبة التثبيط 70.59%، أتى بعدهT.viride بنسبة بلغت 60.39 % ثم الفطرين P.expansum وF.oxysporum بنسبة 30.19% و 25.49%  على الترتيب. كما اختلفت فاعلية الفطريات الناقصة تبعاً لأيام التجربة، وبلغت النسبة الأعلى للتثبيط في اليوم السادس من التجربة، وتوقف نمو الفطر الدعامي بأيام مختلفة تبعاً لنوع الفطر المضاد. بالمقابل أظهرت المركبات الطيارة لجميع الفطريات الناقصة المضادة تأثيراً منشطاً لنمو الفطر الدعامي المدروس.